2020
DOI: 10.48550/arxiv.2007.08057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Tight Approximation Algorithm for the Cluster Vertex Deletion Problem

Abstract: We give the first 2-approximation algorithm for the cluster vertex deletion problem. This is tight, since approximating the problem within any constant factor smaller than 2 is UGC-hard. Our algorithm combines the previous approaches, based on the local ratio technique and the management of true twins, with a novel construction of a "good" cost function on the vertices at distance at most 2 from any vertex of the input graph.As an additional contribution, we also study cluster vertex deletion from the polyhedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As further evidence, for the related problem of cluster vertex deletion [1], we showed that one round of Sherali-Adams has an integrality gap of 5/2, and for every ǫ > 0 there exists r ∈ N such that r rounds of Sherali-Adams has integrality gap at most 2 + ǫ. Indeed, this work can be seen as unifying the approaches of [9] and some of the polyhedral results of [1].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As further evidence, for the related problem of cluster vertex deletion [1], we showed that one round of Sherali-Adams has an integrality gap of 5/2, and for every ǫ > 0 there exists r ∈ N such that r rounds of Sherali-Adams has integrality gap at most 2 + ǫ. Indeed, this work can be seen as unifying the approaches of [9] and some of the polyhedral results of [1].…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, for NP-hard optimization problems (such as FVST), one should not expect that SA r (P ) = P I for some constant r. However, as we will see, good approximations of P I can be extremely useful if we want to approximately optimize over P I . Indeed, despite some recent results [1,5,7,10,13], we feel that the Sherali-Adams hierarchy is underutilized in the design of approximation algorithms, and hope that our work will inspire further applications.…”
Section: The Sherali-adams Hierarchymentioning
confidence: 90%
See 1 more Smart Citation
“…This result is unconditional: it does not rely on P = NP nor the Unique Games Conjecture. We refer the reader to the full version of our paper [4] for precise definitions and for the proofs of Theorems 3 and 4.…”
Section: Our Contributionmentioning
confidence: 99%
“…2.4 we prove Theorem 2. Due to space constraints we omit some proofs and details, for which we refer to the full version of our paper [4]. In particular, [4] contains the proof that Theorem 2 implies Theorem 1, which can be proven similarly as in [10, Proof of Theorem 1], as well as a complexity analysis of Algorithm 1.…”
Section: Overview Of the Proofmentioning
confidence: 99%